Child‐parent cardiac transference is decreased following disrupted/absent early care. Issue 5 (15th February 2021) - Callaghan, Bridget; Pini, Nicolò; Silvers, Jennifer A.; Van Tieghem, Michelle; Choy, Tricia; O'Sullivan, Kaitlin; Fifer, William P.; Tottenham, Nim
Abstract: Parental input shapes youth self‐regulation development, and a lack of sensitive caregiving is a risk factor for youth mental health problems. Parents may shape youth regulation through their influence over biological (including neural) and behavioral development during childhood at both micro (moment‐to‐moment) and macro (global) levels. Prior studies have shown that micro‐level parent‐child interactions shape youth's biology contributing to youth mental health. However, it remains unclear whether prior disrupted/absent care affects those moment‐to‐moment parent‐youth interactions in ways that increase risk for youth psychopathology. In the current study, we calculated transfer entropy on cardiac data from parent‐youth dyads where the youth had either been exposed to disrupted care prior to adoption or not. Transfer Entropy (TE) tracks information flow between two signals, enhancing quantification of directional coupling, allowing for the examination of parent‐child and child‐parent influences. Using this novel approach, we identified lower cardiac information transfer from youth‐to‐parents in dyads where the youth had been exposed to disrupted/absent early care. Moreover we showed that the degree to which the parent's physiology changed in response to youth's physiology was negatively related to the youth's mental health, representing a potential pathway for elevated mental health risk in populations exposed to disrupted/absent early care.